Struktur Dan Komposisi Tumbuhan Bawah Pada Sistem Agroforestri di Desa Warembungan - Aryati Umaternate; Reynold P Kainde; Hengki D. Walangitan (Universitas Sam Ratulangi, 2016)
ABSTRAKStrukrure and Composition of Plants Under the System AgroforestyThe purpose of this study were to analyze and to compare the structure and composition of theundergrowth in agroforestry systems in Warembungan Village. The data collection was done byusing purposive sampling method on 10 plots with size of each plot is 1 m x1 m. Data wereanalyzed using the Importance Value Index (IVI) and Similarity Index (IS) community. Theresults showed that at location A there were 22 species of lower plants where the highest IVI wasAxonopus (29.35 %) and the lowest IVI was Ipomea batatas (0.07 %), then location B there were16 species with Centotheca lappaceae was the highest IVI (26, 27%), and the lowest IVI wasArenga pinnata (0.05 %) and location C there were 11 species of lower plants with Cyathulaprostate was the highest IVI (27.38 %), and the lowest IVI Mimosa pudica (0.65). The highestSimilarity Index (IS) was on location B and C (56.60) compared to the other two locations.Keywords: structure and composition, understory vegetation,agroforestry